A Prospective Assessment of Adverse Events in 3 Digestive Surgery Departments From Central Tunisia. Issue 4 (December 2020) - Letaief, Mondher; El Mhamdi, Sana; Siddiqi, Sameen; Letaief, Rached; Morjane, Abdelwaheb; Hamdi, Abdelaziz
Abstract : Objective: The aim of the study was to prospectively assess the incidence, the preventability, and the factors contributing to adverse events (AEs) in surgical departments of Tunisian hospitals. Methods: A prospective longitudinal study evaluated the incidence of AEs in surgical departments of three university hospitals in central Tunisia. The study followed 1687 admitted patients until their discharge from the hospitals based on a standard two-stage method that first included staff interviews and review of medical records based on 18 criteria and later was followed by an expert review to confirm or reject the presence of an AE. Results: The overall incidence of AEs was 18.1% (95% confidence interval = 16.26–19.94), with an incidence density of 21.6 events per 1000 patient-days. The most frequent AEs were those related to operative procedures (34.9%) and to hospital-acquired infections (30.3%). The multivariate analysis shows that the proportion of AEs increased significantly with intrinsic risk factors (odds ratio [OR] = 2.51, P < 0.001), extrinsic risk factors (OR = 1.38, P = 0.02), length of stay of greater than 7 days (OR = 2.27, P < 0.001), and unplanned admissions (OR = 2.59, P < 0.01). Overall, the major consequences of suffering an AE were that 90% had a prolonged hospital stay, 6% had a permanent disability, and 4% encountered death. More than 60% of the identified AEs were considered to be preventable. Conclusions: Surgical AEs have a significant impact on patient outcomes in terms of length of stay, disability, and mortality, and a considerable proportion of them are preventable. Prospective studies provide better insight regarding AEs under circumstances where hospital records are not optimal. Patient safety programs led by qualified health professionals can reduce patient harm in surgical departments of hospitals in most situations. Abstract : Supplemental digital content is available in the text.